Screening of chickpea germplasm for Ascochyta blight resistance under controlled environment - Pastor, Silvina Estela (2022)
Chickpea is the third most important grain legume in the world after common bean and pea. Ascochyta blight (AB) of chickpea, caused by Ascochyta rabiei, is the most damaging disease of this crop worldwide. Losses may reach 100%, with damage affecting yield and seed quality. AB produces lesions to all aerial plant tissues: leaves, petioles, flowers and pods. The causal agent can survive on or in the seeds and up to four years in stubble. Genetic resistance is the preferred tool for the management of this complex disease. This is the most effective and inexpensive way of controlling biotic stresses and the major goal of many breeding programs. In Argentina, where AB was first detected in 2011, the most widely used commercial varieties, Chañaritos S-156, Norteño, Felipe UNC-INTA and Kiara UNC-INTA, are susceptible to A. rabiei. In this work, 109 genotypes carrying multiple resistance to different pathogens were evaluated against local A. rabiei under controlled conditions. The results showed that all genotypes were affected by this fungus, without occurrence of asymptomatic plants. The genotypes ranged from resistant to highly susceptible. According to disease reaction, the genotypes were classified as: resistant (2.75%),moderately resistant (32.09%), susceptible (60.55%) and highly susceptible (1.83%). This is the first research developed in Argentina to identify resistant genotypes and sources of resistance that contribute to breeding programs.